Mastoid Surgery under Local Anesthesia for Medically Unfit Patients: Techniques and Outcome. (October 2013) - Neumann, Codruta; Yung, Jennifer; Carroll, Paul H.
Objectives: We present the surgical techniques and outcomes of mastoid surgery under local anesthesia in patients who were unfit for general anesthesia. Methods: Five tertiary-referred patients with multiple comorbidities and failed conservative treatment for chronic otitis media were operated on under local anesthesia. No sedation was administered. The principles of cholesteatoma surgery were observed, but the technique was adapted to keep surgical time to a minimum. Results: None of the patients had perioperative problems, and all have dry, waterproof ears with preservation of hearing after surgery. So far, none of the patients have had recurrent or residual disease. Conclusions: Cholesteatoma surgery can be successfully performed with a local anesthetic in patients who are medically unfit for general anesthesia. Surgery requires a good coordination of the operating team in order to shorten the operating time. Otologists should develop and maintain their skills by performing ear surgery with local anesthetic on a regular basis.